The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s13071-015-1122-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of O. volvulus infection via skin exposure to diethylcarbamazine: clinical evaluation of a transdermal delivery technology-based patch

Abstract: BackgroundElimination of onchocerciasis in Africa is now regarded as an achievable goal in many areas. This makes monitoring changes in infection prevalence a key component of control programmes. Monitoring is currently based on determining the presence of O. volvulus microfilariae in skin snips, an invasive, labour-intensive method. The Onchocerciasis Control Programme (OCP) had established procedures to detect O. volvulus infections via the localized skin reaction induced by killing of microfilariae upon ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…MDA combined with vector control has been successful in reducing transmission to elimination in the Americas [ 6 8 ]. Similar trends have been observed in foci in Africa resulting from large-scale implementation of vector control and MDA by the Onchocerciasis Control Program (OCP) and the African Program for Onchocerciasis Control (APOC) [ 9 13 ].…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…MDA combined with vector control has been successful in reducing transmission to elimination in the Americas [ 6 8 ]. Similar trends have been observed in foci in Africa resulting from large-scale implementation of vector control and MDA by the Onchocerciasis Control Program (OCP) and the African Program for Onchocerciasis Control (APOC) [ 9 13 ].…”
Section: Introductionmentioning
confidence: 53%
“…Screening tests using skin snip samples is challenging to implement at large scale due to the relatively labor-intensive nature of the process, the invasiveness, and as local disease burden decreases, a lowered acceptability from the community to be subjected to this process. A transdermal patch that delivers diethylcarbamazine as a local microfilaricide that induces a local skin reaction (a Mazzotti reaction) also can be used as a marker for infection [ 13 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ideally test-and-treat strategies and surveillance should be implemented using tests that are less invasive than the skin snip method. The DEC-patch test ([ 15 18 , 20 ] and see also [ 70 – 72 ]), and Ov-16 serology [ 73 , 74 ] are two possible alternatives. The DEC patch test consists of applying diethylcarbamazine citrate topically to a 6 cm 2 area of skin.…”
Section: Discussionmentioning
confidence: 99%
“…A ready-to-use diethylcarbamazine containing patch, called the LTS-2 patch, has recently been developed, and Awadzi et al 96 have demonstrated that its safety, tolerability, and ability to detect infections are comparable to those of the diethylcarbamazine patch. 96 were present in serum pools from patients infected with other filariae.…”
Section: P0310mentioning
confidence: 99%